Complex thinking, agroecology and pesticides: analysis of the interrelation between science, social movements and the media in the process of social construction of information about toxicity and risk: Pensamento complexo, agroecologia e agrotóxicos: análise da inter-relação entre ciência, movimentos sociais e mídia no processo de construção social das informações sobre toxidade e risco - Lucena Paiva, Raquel (Programa de Pós-graduação em Desenvolvimento, Agricultura e Sociedade da Universidade Federal Rural do Rio de Janeiro (CPDA/UFRRJ), 2019)
This article presents the principles of complex thinking applied to agroecology and how these parameters can be useful to observe contexts and connections not always taken into account in the construction of scientific research related to agrochemicals. The article analyzes the argumentation, the framework and the sources of journalistic material related to the research of the Agência Nacional de Vigilância Sanitária (Anvisa) that evaluated the risks of pesticides for the final consumer. The analysis of the texts presents different possibilities regarding construction of the news and of the sources’ influence over the conduct of the framingapplied to the theme as well as in the interpretation of the data and reporting on scientific research.Keywords: agroecology; complex thinking; environmental sociology; environmental communication.PAIVA, Raquel Lucena. Pensamento complexo, agroecologia e agrotóxicos: análise da inter-relação entre ciência, movimentos sociais e mídia no processo de construção social das informações sobre toxidade e risco. Estudos Sociedade e Agricultura, v. 27, n. 3, p. 547-565, out. 2019.Submitted in June 2019.Accepted in September 2019.